The use of façade sun shading systems for the reduction of indoor and outdoor sound pressure levels. Issue 3 (September 2019) - Fausti, Patrizio; Secchi, Simone; Zuccherini Martello, Nicolò
External shading devices are widely used in recent buildings because they reduce the greenhouse effect due to the solar irradiation through transparent surfaces and the glare effects in interiors. The acoustic effects of these devices have not been well investigated in the literature. In this article, we use a bi-dimensional pressure acoustics finite element model of a shading device attached to a building façade, in frequency domain, to analyse the effects both in the indoor and in the outdoor environments. The finite element model was validated with experimental measurements carried out in a semi-anechoic chamber and then extended to an urban scale to evaluate the effect in the reduction of outdoor noise due to traffic. To improve the acoustic effect of the shading device, a sound absorbing material was added to the bottom side of each louvre. Results of the simulations show that external shading devices tend to increase the sound pressure level over the building façade, while the introduction of the sound absorbing material behind each louvre reduces this problem. The dependencies of the sound pressure level reduction to the geometrical factors of the shading device were investigated by means of the finite element model. The installation of louvres on a building façade can affect also the sound pressure level over a façade of a building placed 20 m away, across a road. In this article, both the effect over the façade of the opposite building and the effect over the urban area between the two buildings are analysed.